MEMBANGUN APLIKASI GAME PETUALANGAN 2D PESAWAT UFO BERBASIS ANDROID - M Budi Hartanto; Yodhi Yuniarthe (Universitas Mitra Indonesia, 2020)
AbstractExtremely fast technological developments Along with the development of hardware that follows the development of software. This development encompasses all sections of life, including in the field of children's games, which at present they tend to prefer digital technology-based games or electronic games. One of the popular games is adventure themed games. In this study the author will build a 2D adventure game for the subject model is UFO aircraft. Many children like adventure and strategy games. Where each game has a target or mission that must be completed in order to proceed to the next stage. The mission given is also not infrequently given a time limit, so he needs to use certain strategies in order to complete it well. The impact of this UFO airplane adventure game Children become accustomed to thinking tactically to find the best strategy. If the first method does not work, he will rack his brain looking for new strategies to complete the mission.